Cross-wire technique for difficult contralateral limb cannulation during endovascular abdominal aneurysm repair for tortuous proximal aortic neck. (24th July 2018) - Lee, Po-Ying; Chen, Po-Lin; Shih, Chun-Che; Chen, I-Ming
Abstract: In selected cases of endovascular aortic repair (EVAR) of an abdominal aortic aneurysm, such as patients with tortuous proximal aortic neck, achieving a successful cannulation can sometimes be difficult. Herein, we described a novel cross-wire technique to help overcome such anatomical variations. During the EVAR procedure among our 5 cases, the main body of the Gore Excluder Stent Graft was deployed through an ipsilateral guidewire. Because of a large angle between the contralateral guidewire and the contralateral short limb of the main body, a successful traditional cannulation was unfeasible. Therefore, the contralateral guidewire was cannulated into the ipsilateral long limb, and the ipsilateral guidewire was cannulated into the contralateral short limb. The contralateral and ipsilateral iliac limb components of the stent graft were deployed through the ipsilateral and contralateral guidewires, respectively. All 5 patients receiving this technique during EVAR of an abdominal aortic aneurysm were free of mortality or any kind of complication at the 1-year follow-up. In conclusion, the cross-wire technique might be safe and effective for EVAR of an abdominal aortic aneurysm when a traditional cannulation is unachievable in selected cases without creating additional percutaneous access or using extra devices.